Evaluasi KPI Terhadap Maturitas BLU: Studi Kasus Poltekkes Pontianak dan Poltekkes Surakarta - Rybob Khomes; Atik Nurwahyuni (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
This study aims to evaluate the indicators on the KPI towards the maturity level of the Public Service Agency (BLU), especially the financial and service aspects at the Poltekkes Kemenkes Pontianak and Poltekkes Kemenkes Surakarta. This study is a continuation of the author's previous research entitled "Correlation between Financial Performance and Service Performance to BLU Maturity at Poltekkes Kemenkes 2021 - 2023". This study uses a qualitative method with a case study approach. The data used are the KPI achievements (financial performance and service performance) of Poltekkes Kemenkes Pontianak and Poltekkes Kemenkes Surakarta in 2021 - 2023 and the maturity value of BLU Poltekkes Kemenkes Pontianak and Poltekkes Kemenkes Surakarta in 2021 - 2023 with the assessment aspects: finance and service, this study also uses statistical test data from previous studies. This study uses an in-depth interview approach with stakeholders and secondary data analysis. The results of the study show that although the KPI achievements at Poltekkes Pontianak and Poltekkes Surakarta have mostly reached the target, the level of BLU maturity in the financial aspect at both Poltekkes is still low, namely in the range of 1.50 - 2.97, meaning it is still at level 1 and level 2, so recommendations are needed to improve KPI indicators in financial performance to truly support BLU maturity.